ACCOMPLISHMENT OF THE ECONOMICS OF SUSTAINABLE DEVELOPMENT AS AN OPPORTUNITY TO BUILD A COMPETITIVE ADVANTAGE - Zaremba-Warnke, Sabina (Ekonomia i Prawo. Economics and Law, 2015)
Currently creating economics of sustainable development is an alternative concept in relation to neoclassical economics. The aim of economics of sustainable development is sustainable management, which means to guarantee high economic, ecological and socio-cultural standards for present and future generations within the limits of environment’s natural resistance. The accomplishment of sustainable development concept requires the activeness of all socio-economic subjects, particulary the ones which should play a key role - enterprises. Although, more companies pay attention to social results of their activities, so the ones which really act in accordance with the principles of sustainable development, still constitute a minority on the market. The assumption of economics of sustainable development, in practice - enterprise management come to so called three strategic paths i.e. effectiveness, cohesion and sufficiency. It also leads to fulfill sustainability criteria, which can be divided into three main groups i.e. ecological, economic and socio-cultural ones. Accomplishment of sustainable development assumptions constitutes an opportunity to build a durable competitive advantage in enterprises. The purpose of this article is to characterize the assumptions of economics of sustainable development in relation to enterprise management and to point out a possibility to build a competitive advantage by enterprises acting in accordance with sustainable development principles.